The linkage between child poverty and family poverty with the paradox of education and remittance: A case study in Chiang Mai, Thailand - Sun Gue Yang (2018)
© Serials Publications Pvt. Ltd. This paper investigates the causes of child poverty through the linkage to family poverty. It takes Chiang Mai, Thailand as a case study with econometric methods and empirical analysis. It develops two hypotheses that, first, child poverty and family poverty are caused mainly from the expenditure that is spent on the education of the child, and second, older parents are more likely to be in poverty than younger parents. Two models are estimated, the poverty due to debt and remittance to family. The results from a door-to-door survey in villages in the suburb areas of Chiang Mai and three econometric methods reveal that poverty is mainly from the debt that families make in order to send their children to obtain higher level of education. Moreover, the chances of children remitting money back to their family, after going through the hardship to send them off to better education to change their future socio-economic status, are low. This paradox can be demonstrated as the negative impacts of education to poverty reduction.